Adhesivo a Base de Tanino en Tableros Contrachapados Para Interiores - Devlieger S., Francis; Cuevas D., Héctor (Bosque (Valdivia), 1984)
Unfortified Tannin extracts of quebracho (Schinopsis spp) were catalysed with formaldehyde solution (35% aqueous) to produce adhesive resins used in the manufacture of interior grade plywood of Tepa (Laurelia philippiana). The pH of the glue mixture was in the range of 7.1 - 7.5. Some properties of Tannin-formaldehide were examined especially the viscosity and pot life. Assembly and pressing conditions were similar to those used for the construction of interior grade plywood. Results of the bond quelities evalued by comparison with German Specification and industrial plywood made with Urea Formaldehyde. The average value of Shear Strength for bonding wood veneer of Tepa was 2,2 M Pa after soaking test in cold water (20°C) for 24 hr.